Resin composition, resin film and metal-clad laminate
By using high proportion of cubic quartz phase silica particles for compositeization in polyimide-based resin, the challenge of polyimide in low dielectric is solved, and low dielectric loss in high-frequency signal transmission is achieved and low thermal expansion effect, suitable for FPC insulating resin layer of high-frequency electronic devices.
Patent Information
- Application Number
- CN202011446201.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2019-12-27
- Filing Date
- 2020-12-11
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2040-12-11
AI Technical Summary
The prior art has difficulty in achieving low dielectricization of polyimides, especially in the adhesion strength and thermal expansion coefficient during multilayering, while maintaining high heat resistance and excellent adhesion properties.
By using high proportion of crquartz phase silica particles in the polyimide-based resin for composite, dielectric characteristics are improved, and dielectric of the resin film is optimized by mixing the particle size distribution and crystallization structure of the silica particles. Loss and thermal expansion coefficients.
The effect of low dielectric loss and low thermal expansion in high-frequency signal transmission is achieved, and the FPC insulating resin layer suitable for high-frequency electronic equipment is improved, and the heat resistance and adhesion of the resin film are improved.
Smart Images

Figure BDA0002831177720000051 
Figure BDA0002831177720000052 
Figure BDA0002831177720000061
Abstract
Description
Technical Field
[0001] The present invention relates to a resin composition, a resin film and a metal-clad laminate which can be effectively used as, for example, a circuit board material. Background Art
[0002] In recent years, with the miniaturization, lightness and space saving of electronic equipment, the use of thin and lightweight flexible printed circuit (FPC) has increased. FPC can be installed in a three-dimensional and high-density manner even in a limited space, so its use is expanded to the wiring of the movable part of the electronic equipment, or parts such as cables and connectors. In addition to these, the high-speed or high-performance development of communication equipment continues, and FPC corresponding to high-frequency transmission signals for achieving high transmission speeds is also needed.
[0003] As a topic when transmitting high-frequency signals, there is a transmission loss in the transmission path of the signal. If the transmission loss is large, undesirable conditions such as electrical signal loss or signal delay will occur. In order to correspond to high frequency, the reduction of the transmission loss brought by the low dielectric constant and low dielectric loss tangent of the insulating resin layer of FPC becomes important. Therefore, in the FPC used for high-frequency signals, liquid crystal polymers or fluorine-based resins with low dielectric constant and low dielectric loss tangent are used as insulating resin layers. However, although liquid crystal polymers have excellent dielectric properties, there is room for improvement in heat resistance or adhesion with metal foil, and fluorine-based resins are not good in operability due to their high thermal expansion coefficient.
[0004] As an insulating resin with excellent heat resistance or adhesion to metal foil, polyimide is also used. However, in general, compared with liquid crystal polymers or fluorine-based resins, the dielectric properties of polyimide are poor. As a method for making aromatic polyimide low dielectric, there is a method of incorporating aliphatic structures into the resin skeleton. However, the advantages of incorporating aliphatic structures into the resin skeleton are in most cases a trade-off relationship with the required characteristics of FPC such as heat resistance or dimensional stability. As other methods, when using special monomers or expensive fluorine-based monomers, in order to achieve low dielectric while maintaining excellent heat resistance and the required characteristics of FPC only with the skeleton of polyimide, there are various obstacles in terms of cost and productivity.
[0005] Therefore, a method of improving the properties by compounding a resin with a different material is known. For example, Patent Document 1 reports a polyimide composition having excellent thermal conductivity by compounding aluminum nitride or silicon nitride powder with a specific polyimide.
[0006] In addition, in Patent Document 2, by adding cristobalite silica to epoxy resin, the occurrence of warpage or cracks in a semiconductor package can be suppressed.
[0007] Composites are also effective in improving dielectric properties, and Patent Document 3 proposes a resin film with low dielectric loss tangent and low thermal expansion by combining amorphous silica with a thermosetting polyimide resin synthesized from bismaleimide and an elastomer. In addition, Patent Document 4 suggests a method for producing a low dielectric polyimide film by combining polyimide and fluororesin particles.
[0008] [Prior art literature]
[0009] [Patent Document]
[0010] [Patent Document 1] Japanese Patent No. 3551687
[0011] [Patent Document 2] Japanese Patent Application Publication No. 2019-1937
[0012] [Patent Document 3] Japanese Patent Application Publication No. 2018-12747
[0013] [Patent Document 4] Japanese Patent No. 6387181 Summary of the invention
[0014] [Problems to be solved by the invention]
[0015] As described above, it is expected to develop a polyimide that achieves low dielectric properties while maintaining high heat resistance or excellent adhesion. However, in Patent Document 3, it is limited to a thermosetting resin, and there are problems with the adhesion strength when multilayered. In addition, in Patent Document 4, it is compounded with a relatively expensive fluororesin filler, and there are problems such as an increased thermal expansion coefficient.
[0016] Furthermore, in the prior art of composite formation, emphasis has been placed on the composition of the filler, and little attention has been paid to its crystal structure.
[0017] Therefore, an object of the present invention is to provide a resin composition and a resin film that can cope with the increase in the frequency of electronic devices by further improving the dielectric properties of polyimide.
[0018] [Technical means to solve the problem]
[0019] The present inventors have found that, in composite formation of a polyimide-based resin and silica particles, dielectric properties are improved when silica particles having a higher proportion of a cristobalite phase than amorphous silica are used as silica particles, thereby completing the present invention.
[0020] That is, the resin composition of the present invention contains: a solid content of an organic compound including polyamic acid or polyimide, and silica particles.
[0021] The content of the silica particles is in the range of 10 wt % to 85 wt % (wherein the polyamic acid is converted to imidized polyimide) relative to the total amount of the solid content and the total amount of the silica particles.
[0022] As for the silica particles as a whole, the ratio of the total area of the peaks derived from the cristobalite crystal phase and the quartz crystal phase in the range of 2θ=10° to 90° in the X-ray diffraction analysis spectrum using CuKα rays to the total peak area derived from SiO2 is 20 weight % or more.
[0023] The median particle size D in the frequency distribution curve of the silica particles obtained by volume-based particle size distribution measurement using a laser diffraction scattering method in the resin composition of the present invention is 50 It can be in the range of 6 μm to 20 μm.
[0024] In the resin composition of the present invention, 90% by weight or more of the silica particles having a particle size of 3 μm or more may have a circularity of 0.7 or more.
[0025] In the resin composition of the present invention, 90% by weight or more of the silica particles may have a true specific gravity of 2.3 or more.
[0026] The resin film of the present invention is a resin film having a single or multiple polyimide layers, at least one of which is a crystalline silica-containing polyimide layer formed from any of the resin compositions, and the thickness of the crystalline silica-containing polyimide layer is in the range of 15 μm to 200 μm.
[0027] In the resin film of the present invention, the ratio of the thickness of the crystalline silica-containing polyimide layer to the entire thickness of the resin film may be 50% or more.
[0028] The resin film of the present invention can have a relative dielectric constant of 3.1 or less at a frequency of 3 GHz to 20 GHz when measured using a split post dielectric resonator (SPDR).
[0029] The resin film of the present invention can have a dielectric loss tangent of 0.005 or less at a frequency of 3 GHz to 20 GHz when measured by a split dielectric resonator (SPDR).
[0030] The thermal expansion coefficient of the resin film of the present invention can be 50 ppm / K or less.
[0031] The metal-clad laminate of the present invention includes an insulating resin layer and a metal layer laminated on at least one surface of the insulating resin layer, and at least one layer of the insulating resin layer includes any of the above-mentioned resin films.
[0032] [Effects of the Invention]
[0033] The resin composition of the present invention contains silicon dioxide particles with a specific crystalline structure in addition to the original heat resistance of polyimide, so the dielectric properties are excellent. Therefore, the resin composition and resin film of the present invention are particularly suitable for use as circuit substrate materials such as FPC in electronic devices requiring high-speed signal transmission. Specifically, it is suitable for the insulating resin layer of the FPC of mobile devices such as smart phones that process high-frequency signals or the insulating resin layer of the FPC for vehicle-mounted devices that require heat resistance. DETAILED DESCRIPTION
[0034] Hereinafter, embodiments of the present invention will be described.
[0035] [Resin composition]
[0036] A resin composition according to one embodiment of the present invention is a resin composition containing a solid content of an organic compound including polyamic acid or polyimide and silica particles.
[0037] The content of the silica particles is in the range of 10 wt % to 85 wt % relative to the total amount of the solid content and the total amount of the silica particles.
[0038] As for the silica particles as a whole, the ratio of the total area of the peaks derived from the cristobalite crystal phase and the quartz crystal phase in the range of 2θ=10° to 90° of the X-ray diffraction analysis spectrum using CuKα rays to the total area of all peaks derived from SiO2 is 20% by weight or more. The resin composition may be a varnish (resin solution) containing polyamic acid, or a polyimide solution containing a solvent-soluble polyimide.
[0039] [Solid content of organic compound]
[0040] The so-called solid content of organic compounds refers to the remaining solid content after removing the solvent and inorganic solid content from the resin composition. That is, the solid content of organic compounds can contain polyamic acid or polyimide, and as an arbitrary component, can contain non-volatile organic compounds such as resins, crosslinking agents, organic fillers, plasticizers, hardening accelerators, coupling agents, organic pigments, organic flame retardants, and fillers other than polyimide. Here, as resins other than polyimide, for example, epoxy resins, fluororesins, olefin resins, polyether resins, polyester resins, etc. can be listed. As crosslinking agents, amino compounds (crosslinking amino compounds) having at least two primary amino groups described later as functional groups can be listed. As organic fillers, for example, liquid crystal polymer particles, fluorine polymer particles, polyether resin particles, olefin resin particles, etc. can be listed.
[0041] The content of polyamic acid or polyimide in the solid component of organic compound is preferably more than 60 weight %, more preferably more than 70 weight %, most preferably more than 80 weight %.If the content of polyamic acid or polyimide is less than 60 weight %, the toughness of resin is reduced, and the film retention during the formation of resin film is reduced.Moreover, in the case of polyamic acid, it is set to be converted into imidized polyimide to calculate weight ratio.
[0042] [Polyamic acid or polyimide]
[0043] Polyimide is generally represented by the following general formula (1). Such polyimide can be produced by a conventional method of using substantially equimolar amounts of a diamine component and an acid dianhydride component to polymerize in an organic polar solvent. In such a case, in order to set the viscosity to a desired range, the molar ratio of the acid dianhydride component to the diamine component can be adjusted, and the range is preferably set to a molar ratio of 0.98 to 1.03, for example.
[0044] [Chemistry 1]
[0045]
[0046] Here, Ar1 is a tetravalent organic group having one or more aromatic rings, and Ar2 is a divalent organic group having one or more aromatic rings. Furthermore, Ar1 can be said to be a residue of an acid dianhydride, and Ar2 can be said to be a residue of a diamine. In addition, n represents the number of repetitions of the structural unit of the general formula (1), which is 200 or more, preferably 300 to 1000.
[0047] As the acid dianhydride, for example, an aromatic tetracarboxylic dianhydride represented by O(OC)2-Ar1-(CO)2O is preferred, and examples thereof include acid dianhydrides that provide the following aromatic acid anhydride residues as Ar1.
[0048] [Chemistry 2]
[0049]
[0050] The acid dianhydride may be used alone or in combination of two or more. Among these, it is preferred to use one selected from pyromellitic dianhydride (PMDA), 3,3',4,4'-biphenyl tetracarboxylic dianhydride (BPDA), 3,3',4,4'-benzophenone tetracarboxylic dianhydride (BTDA), 3,3',4,4'-diphenyl sulfone tetracarboxylic dianhydride (DSDA), and 4,4'-oxydiphthalic dianhydride (ODPA).
[0051] As the diamine, for example, an aromatic diamine represented by H2N-Ar2-NH2 is preferred, and examples thereof include aromatic diamines providing the following aromatic diamine residues as Ar2.
[0052] [Chemistry 3]
[0053]
[0054] Among these diamines, diaminodiphenyl ether (DAPE), 2,2'-dimethyl-4,4'-diaminobiphenyl (m-TB), paraphenylene diamine (p-PDA), 1,3-bis(4-aminophenoxy)benzene (TPE-R), 1,3-bis(3-aminophenoxy)benzene (APB), 1,4-bis(4-aminophenoxy)benzene (TPE-Q), 2,2-bis[4-(4-aminophenoxy)phenyl]propane (2,2-bis[4-(4-aminophenoxy)phenyl]propane (2,2-bis[4-(4-aminophenoxy)phenyl]propane (2,2-bis[4-(4-aminophenoxy)phenyl]propane (2,2-bis[4-(4-aminophenoxy)phenyl]propane (2,2-bis[4-(4-aminophenoxy)phenyl]propane (2,2-bis[4-(4-aminophenoxy)phenyl]propane (2,2-bis[4-(4-aminophenoxy)phenyl]propane (2,2-bis[4-(4-aminophenoxy)phenyl]propane (2,2-bis[4-(4-aminophenoxy)phenyl]propane (2,2-bis[4-(4-aminophenoxy)phenyl]propane (2,2-bis[4-(4-aminophenoxy)phenyl]propane (2,2-bis[4-(4-aminophenoxy)phenyl]propane (2,2-bis[4-(4-aminophenoxy)phenyl]propane phenoxy)phenyl]propane, BAPP), and 2,2-bis(trifluoromethyl)benzidine (TFMB) are preferred.
[0055] Polyimide can be produced by reacting an acid dianhydride with a diamine compound in a solvent to generate a polyamic acid as a precursor and then heating it for ring closure (imidization). For example, an acid dianhydride and a diamine compound are dissolved in an organic solvent in approximately equimolar amounts, and stirred at a temperature in the range of 0°C to 100°C for 30 minutes to 72 hours to perform a polymerization reaction, thereby obtaining a polyamic acid. During the reaction, the reaction components are dissolved in an organic solvent in such a manner that the generated precursor becomes within the range of 5% by weight to 30% by weight, preferably within the range of 10% by weight to 20% by weight. As the organic solvent used in the polymerization reaction, for example, N,N-dimethylformamide (DMF), N,N-dimethylacetamide (DMAc), N,N-diethylacetamide, N-methyl-2-pyrrolidone (NMP), 2-butanone, dimethyl sulfoxide (DMSO), hexamethylphosphoramide, N-methylcaprolactam, dimethyl sulfate, cyclohexanone, dioxane, tetrahydrofuran, diethylene glycol dimethyl ether, triethylene glycol dimethyl ether, cresol, etc. It is also possible to use two or more of these solvents, and further, it is also possible to use aromatic hydrocarbons such as xylene and toluene. In addition, there is no particular limitation on the amount of such an organic solvent used, and it is preferably used in an amount adjusted to a concentration of about 5% by weight to 30% by weight of the polyamic acid solution obtained by the polymerization reaction.
[0056] The synthesized polyamic acid is usually advantageously used as a reaction solvent solution, and can be concentrated, diluted or replaced with other organic solvents as needed to form a resin composition. The method of imidizing the polyamic acid is not particularly limited, for example, it can be preferably used in the solvent, under the temperature conditions within the range of 80°C to 400°C, to spend 1 hour to 24 hours to perform the heat treatment.
[0057] The polyimide may be a thermoplastic polyimide or a thermosetting polyimide. The so-called "thermoplastic polyimide" is generally a polyimide whose glass transition temperature (Tg) can be clearly confirmed, but in the present invention, it means: a polyimide having a storage elastic coefficient of 1.0×10 8 Pa or more, and the storage elastic coefficient at 300°C is less than 3.0×10 7In addition, the so-called "non-thermoplastic polyimide" is generally a polyimide that does not soften even when heated and exhibits adhesiveness, but in the present invention, it means: a polyimide having a storage elastic modulus of 1.0×10 9 Pa and the storage elastic coefficient at 300°C is 3.0×10 8 Pa or more polyimide.
[0058] [Silicon dioxide particles]
[0059] As silica particles, as long as crystalline silica particles are included. In addition, amorphous silica particles may also be included. By allocating crystalline silica particles in the resin composition, the dielectric loss tangent when forming a resin film can be reduced. With regard to the viewpoint of seeking to form a resin film with low dielectric loss tangent, it is particularly preferred to use silica particles with cristobalite crystalline phase as crystalline silica particles. Compared with general silica particles, the dielectric properties of silica particles with cristobalite crystalline phase are very excellent (for example, the dielectric loss tangent at 10GHz in the silica particles containing more than 90% by weight of cristobalite crystalline phase is about 0.0008 in terms of monomer), which can greatly contribute to the low dielectric loss tangent of the resin film.
[0060] The median particle size D in the frequency distribution curve of the silica particles obtained by the volume-based particle size distribution using the laser diffraction scattering method is 50 The median diameter D is in the range of 6 μm to 20 μm, preferably in the range of 8 μm to 15 μm. If it is in the above range, the dielectric properties are effectively improved, and a resin film with low dielectric properties can be obtained without deteriorating the surface smoothness when it is mixed in a resin film. 50 If the median diameter D is below the above range, the surface area of the silica particles increases, and the adsorbed water on the surface of the silica particles may affect the dielectric properties. 50 If the amount exceeds the above range, the unevenness may appear as unevenness on the film surface, thereby deteriorating the smoothness of the film surface.
[0061] In addition, as silica particles, it is preferred to use spherical silica particles. Spherical silica particles refer to silica particles whose shape is close to spherical and whose average major diameter to average minor diameter ratio is 1 or close to 1. In addition, in order to improve the dispersibility of silica particles and the improvement of dielectric properties, more than 90% by weight of silica particles with a particle size of more than 3 μm are preferably circularities of more than 0.7, more preferably more than 0.9. The circularity of silica particles can be obtained by image analysis, assuming a circle with the same projected area as the particles photographed, and by the ratio of the circumference of the circle to the circumference of the particles. If the circularity is less than 0.7, the surface area increases, which sometimes has an adverse effect on dielectric properties, and then the increase in viscosity when being deployed in the resin solution becomes larger, which is difficult to handle. In addition, it is preferably a value substantially corresponding to the value of the circularity in the sphericity obtained three-dimensionally.
[0062] In order to improve the dispersibility of silica particles and the effect of improving dielectric properties, the silica particles preferably have a true specific gravity of 2.3 or more. If the true specific gravity is less than 2.3, it is suggested that the crystallinity of the silica particles is low and the effect of improving dielectric properties becomes small.
[0063] The silica particles can be subjected to surface treatment. Existing techniques can be used for surface treatment, for example, preferably by modification using corona treatment, plasma treatment, ultraviolet (ultraviolet, UV) treatment, or functionalization treatment using silane coupling agents, etc. The silica particles are subjected to surface treatment, and alkyl, amino and alkoxy groups are given to the particle surfaces, thereby improving the affinity with the solvent or polyamic acid, or improving the repulsion between the particles, thereby improving the dispersibility of the silica particles and the long-term stability of the varnish.
[0064] From the viewpoint of seeking to form a resin film with low dielectric loss tangent, as the aggregate of the silica particles used, the total area of the peaks of the quartz crystal phase and the quartz crystal phase in the range of 2θ=10° to 90° of the X-ray diffraction analysis spectrum of CuKα rays is preferably 20% by weight or more, more preferably 40% by weight or more, and ideally 80% by weight or more. By increasing the proportion of the quartz crystal phase and / or the quartz crystal phase of the entire silica particles, it is possible to seek a further low dielectric loss tangent of the polyimide. If the area ratio of the peaks of the quartz crystal phase and the quartz crystal phase in the entire silica particles is less than 20% by weight, the effect of improving the dielectric properties is unclear. The ratio of the cristobalite crystalline phase can be obtained by using an X-ray diffractometry (XRD) method using α radiation to determine the ratio of the total area of the diffraction peaks derived from the cristobalite crystalline phase and the quartz crystalline phase measured within the range of 10°≦2θ≦90° to the total area of the diffraction peaks derived from all silica particles within the range. Furthermore, in the case where the peak of the object in the X-ray diffraction analysis spectrum is difficult to separate from the broad peak of the amorphous phase or overlaps with other crystalline phase peaks, various existing analysis methods, such as the internal standard method or the PONKCS method, can be used.
[0065] As a preferred embodiment, a collection of silica particles having a ratio of cristobalite crystal phase of 50% or more by weight can be used. As a further preferred embodiment, amorphous silica particles can be used instead of a part (e.g., less than 80% by weight of the whole) of the collection of silica particles having a ratio of cristobalite crystal phase of 90% or more by weight. The use of amorphous silica particles as a substitute can be carried out as needed, thereby having the advantages of being able to reduce costs, adjust high-density filling and solution viscosity, and being able to prepare a resin composition with excellent operability.
[0066] Furthermore, the silica particles can be appropriately selected from commercial products and used. As crystalline silica particles, for example, spherical quartz silica powder (manufactured by Nihon Steel Chemical & Materials Co., Ltd., trade name: CR10-20) can be preferably used. In addition, as amorphous silica particles that can be combined with crystalline silica particles, spherical amorphous silica powder (manufactured by Nihon Steel Chemical & Materials Co., Ltd., trade name: SC70-2, trade name: SP40-10) etc. can be used. Furthermore, two or more different silica particles can also be used as silica particles.
[0067] [Mixture composition]
[0068] Relative to the solid component of the organic compound in the resin composition and the total amount of silicon dioxide particles, the content of the silicon dioxide particles in the resin composition is in the range of 10% by weight to 85% by weight (wherein polyamic acid is converted into imidized polyimide), preferably in the range of 10% by weight to 80% by weight, more preferably in the range of 15% by weight to 75% by weight. If the containing ratio of silicon dioxide particles is less than 10% by weight, the effect of reducing dielectric loss tangent cannot be fully obtained. In addition, if the containing ratio of silicon dioxide particles exceeds 85% by weight, the characteristics such as the adhesion of polyimide are reduced, and particularly if the containing ratio of silicon dioxide particles exceeds 80% by weight, it becomes brittle when forming resin film, and bending property is reduced, and in the case of forming resin film, the viscosity of resin composition becomes high, and workability is also reduced.
[0069] [Optional Ingredients]
[0070] The resin composition of the present embodiment may contain an organic solvent. As an organic solvent, for example, N, N-dimethylformamide (DMF), N, N-dimethylacetamide (DMAc), N, N-diethylacetamide, N-methyl-2-pyrrolidone (NMP), 2-butanone, dimethyl sulfoxide (DMSO), hexamethylphosphoramide, N-methylcaprolactam, dimethyl sulfate, cyclohexanone, dioxane, tetrahydrofuran, diethylene glycol dimethyl ether, triethylene glycol dimethyl ether, cresol, etc. These solvents may also be used in combination of two or more, and further aromatic hydrocarbons such as xylene and toluene may also be used in combination. As the content of the organic solvent, there is no particular limitation, and it is preferably used in an amount adjusted to a concentration of polyamic acid or polyimide of about 5% by weight to 30% by weight.
[0071] The resin composition of the present invention can be appropriately prepared as needed inorganic fillers, inorganic pigments, inorganic flame retardants, inorganic heat dissipating agents, etc. other than silica particles as arbitrary components within the scope of not damaging the effect of the invention. As inorganic fillers other than silica particles, for example, aluminum oxide, magnesium oxide, beryllium oxide, niobium oxide, titanium oxide, boron nitride, aluminum nitride, silicon nitride, aluminum fluoride, calcium fluoride, magnesium fluoride, potassium fluorosilicate, phosphonic acid metal salts, etc. These can be used alone or in combination of two or more.
[0072] [Viscosity]
[0073] As a viscosity range for improving the handling property when applying the resin composition and facilitating the formation of a coating film of uniform thickness, the viscosity of the resin composition is preferably set in the range of 3000 cps to 100000 cps, and more preferably in the range of 5000 cps to 50000 cps. If the viscosity deviates from the above range, defects such as uneven thickness and streaks are likely to occur on the film during coating operations using a coater or the like.
[0074] [Preparation of resin composition]
[0075] When preparing a resin composition, for example, silica particles can be directly prepared in a resin solution of polyamic acid made using an arbitrary solvent. Alternatively, in consideration of the dispersibility of silica particles, silica particles can also be prepared in advance in a reaction solvent in which any of the acid dianhydride component and diamine component as the raw material of polyamic acid is put, and then another raw material is put into polymerization under stirring. In either method, silica particles can be put into all at once, or added little by little in fractions. In addition, the raw materials can also be put in together, or mixed little by little in fractions.
[0076] [Resin film]
[0077] The resin film of the present embodiment is a resin film having a single or multiple polyimide layers, and at least one layer, preferably all of the polyimide layers may be crystalline silica-containing polyimide layers formed from the resin composition.
[0078] In the resin film, the thickness of the polyimide layer containing crystalline silica formed by the resin composition is preferably in the range of 15 μm to 200 μm, and more preferably in the range of 20 μm to 150 μm. If the thickness of the polyimide layer containing crystalline silica is less than 15 μm, the silica particles protrude on the surface of the resin film, and the surface smoothness deteriorates. On the contrary, if the thickness of the polyimide layer containing crystalline silica exceeds 200 μm, there is a tendency to be disadvantageous in terms of reduced bendability of the resin film, etc.
[0079] The overall thickness of the resin film is, for example, in the range of 15 μm to 200 μm, preferably in the range of 20 μm to 200 μm, and more preferably in the range of 25 μm to 200 μm. If the thickness of the resin film is less than 15 μm, it is easy to cause unfavorable conditions such as wrinkles on the metal foil and rupture of the resin film during the conveying process when manufacturing the metal-clad laminate. On the contrary, if the thickness of the resin film exceeds 200 μm, there is a tendency to be disadvantageous in terms of reduced bendability of the resin film.
[0080] In addition, the ratio of the thickness of the polyimide layer containing crystalline silica to the thickness of the entire resin film is preferably 50% or more relative to the total thickness. If the ratio of the thickness of the polyimide layer containing crystalline silica to the thickness of the entire resin film is less than 50%, the dielectric properties cannot be sufficiently improved.
[0081] The method for forming the crystalline silicon dioxide-containing polyimide layer can be adopted without particular limitation, and a conventional method can be adopted. The most representative example thereof is shown here.
[0082] First, the resin composition is directly cast onto an arbitrary support substrate to form a coating film. Next, the coating film is dried to a certain extent at a temperature below 150°C and the solvent is removed. When the resin composition contains polyamic acid, the coating film is heat-treated for about 5 minutes to 30 minutes at a temperature range of 100°C to 400°C, preferably 130°C to 360°C, for further imidization. In this way, a polyimide layer containing crystalline silica can be formed on the support substrate.
[0083] In the case of a polyimide layer with more than two layers, after applying the first polyamic acid resin solution and drying, the second polyamic acid resin solution is applied and dried. Thereafter, similarly, the third polyamic acid resin solution, the fourth polyamic acid resin solution, ... are applied in sequence and dried according to the required number of times. Afterwards, it is advisable to perform a heat treatment for about 5 minutes to 30 minutes in the temperature range of 100°C to 400°C for imidization. If the imidization temperature is lower than 100°C, there is a concern that the dehydration ring-closing reaction of the polyimide cannot be fully carried out. On the contrary, if it exceeds 400°C, there is a concern that the polyimide layer will deteriorate.
[0084] Alternatively, the imidization process can be repeated by subjecting any imidized polyimide layer to appropriate surface treatment, and then repeating the steps of coating, drying and imidization of the resin solution to re-stack the layers. In this case, imidization in the intermediate steps does not need to be completed, and imidization can be completed in the final step.
[0085] In addition, any imidized polyimide layer may be thermally pressure-bonded to a separately formed resin film.
[0086] Furthermore, the resin film may be in a state of being attached to a supporting substrate.
[0087] Another example of forming a polyimide layer containing crystalline silicon dioxide is given.
[0088] First, the resin composition is cast onto an arbitrary supporting substrate to form a film. The film-shaped product is heated and dried on the supporting substrate to form a self-supporting gel film. After the gel film is peeled off from the supporting substrate, if the resin composition contains polyamic acid, it is further heat-treated at a high temperature to imidize it to form a polyimide resin film.
[0089] The supporting substrate for forming the polyimide layer containing crystalline silicon dioxide is not particularly limited, and a substrate of any material can be used. In addition, when forming the resin film, it is not necessary to form a completely imidized resin film on the substrate. For example, the resin film in the polyimide precursor state in a semi-hardened state can also be separated from the supporting substrate by methods such as peeling, and the imidization is completed after separation to form the resin film.
[0090] The resin film may include only a polyimide layer containing an inorganic filler (including the polyimide layer containing crystalline silica), or may have a polyimide layer that does not contain an inorganic filler. In the case where the resin film is set to a multilayer laminated structure, if the improvement of dielectric properties is taken into account, it is preferred that all layers contain inorganic fillers. Among them, by setting the adjacent layer of the polyimide layer containing an inorganic filler as a layer that does not contain an inorganic filler, or as a layer with a low content thereof, it is possible to have a favorable effect of preventing the inorganic filler from slipping during processing. In the case of a polyimide layer that does not contain an inorganic filler, its thickness is preferably set to within the range of 1 / 100 to 1 / 2 of the polyimide layer containing an inorganic filler, and preferably within the range of 1 / 20 to 1 / 3. In the case of a polyimide layer that does not contain an inorganic filler, if the polyimide layer is in contact with a metal layer, the adhesion between the metal layer and the insulating resin layer is improved.
[0091] The coefficient of thermal expansion (CTE) of the resin film is not particularly limited, but is preferably within the range of 10×10 -6 / K~50×10 -6 / K (10ppm / K to 50ppm / K), more preferably 15×10 -6 / K~40×10 -6 / K (15ppm / K~40ppm / K). If the thermal expansion coefficient of the resin film is less than 10×10 -6 / K, the metal-clad laminate is prone to curling and poor in handling. On the other hand, if the thermal expansion coefficient of the resin film exceeds 50×10 -6 / K, the dimensional stability as an electronic material such as a flexible substrate tends to be poor, and the heat resistance also tends to be reduced.
[0092] [Dielectric loss tangent]
[0093] When the resin film is used as an insulating resin layer of a circuit substrate, for example, in order to reduce the dielectric loss during high-frequency signal transmission, as a whole film, the dielectric loss tangent (Tanδ) at 3GHz to 20GHz when measured by a split dielectric resonator (SPDR) is preferably 0.005 or less, and more preferably 0.004 or less. In order to improve the transmission loss of the circuit substrate, it is particularly important to control the dielectric loss tangent of the insulating resin layer. By setting the dielectric loss tangent to within the range, the effect of reducing the transmission loss is increased. Therefore, when the resin film is used as an insulating resin layer of a high-frequency circuit substrate, for example, the transmission loss can be efficiently reduced. If the dielectric loss tangent at 3GHz to 20GHz exceeds 0.005, when the resin film is used as an insulating resin layer of a circuit substrate, it is easy to produce undesirable conditions such as the loss of electrical signals on the transmission path of the high-frequency signal. The lower limit of the dielectric loss tangent at 3GHz to 20GHz is not particularly limited, but it is necessary to consider the physical property control when the resin film is used as an insulating resin layer of a circuit substrate.
[0094] [Relative dielectric constant]
[0095] When the resin film is used as an insulating resin layer of a circuit substrate, for example, in order to ensure impedance matching, the relative dielectric constant of the film as a whole at 3 GHz to 20 GHz when measured by a split dielectric resonator (SPDR) is preferably 3.1 or less. If the relative dielectric constant at 3 GHz to 20 GHz exceeds 3.1, when the resin film is used as an insulating resin layer of a circuit substrate, the dielectric loss will be deteriorated, and the loss of the electrical signal in the transmission path of the high-frequency signal will be increased.
[0096] [Metal-clad laminate]
[0097] The metal-clad laminate of the present embodiment is a metal-clad laminate comprising an insulating resin layer and a metal layer laminated on at least one surface of the insulating resin layer, wherein at least one layer of the insulating resin layer comprises the resin film. The metal-clad laminate may be a single-sided metal-clad laminate having a metal layer only on one side of the insulating resin layer, or may be a double-sided metal-clad laminate having metal layers on both sides of the insulating resin layer.
[0098] [Insulating resin layer]
[0099] The insulating resin layer includes a single layer or multiple layers, including a layer including the resin film. For example, the resin film may form a non-thermoplastic polyimide layer as a main layer of the insulating resin layer for ensuring mechanical characteristics or thermal properties. In addition, the resin film may form a thermoplastic polyimide layer as an adhesive layer that bears the bonding strength with a metal layer such as copper foil. In addition, the so-called "main layer" refers to a layer that occupies 50% or more of the total thickness of the insulating resin layer.
[0100] In addition, the metal-clad laminate of the present embodiment does not exclude the use of an adhesive for bonding the polyimide layer containing an inorganic filler to the metal foil. In the case where an adhesive layer is interposed in a double-sided metal-clad laminate having a metal layer on both sides of the insulating resin layer, in order not to damage the dielectric properties, the thickness of the adhesive layer is preferably set to less than 30% of the thickness of the entire insulating resin layer, and more preferably less than 20%. In addition, in the case where an adhesive layer is interposed in a single-sided metal-clad laminate having a metal layer only on one side of the insulating resin layer, in order not to damage the dielectric properties, the thickness of the adhesive layer is preferably set to less than 15% of the thickness of the entire insulating resin layer, and more preferably less than 10%. In addition, the adhesive layer constitutes a part of the insulating resin layer, and is therefore preferably a polyimide layer. In the case where the polyimide layer containing crystalline silica constitutes the main layer of the insulating resin layer, from the viewpoint of imparting heat resistance, the glass transition temperature of the polyimide layer containing crystalline silica is preferably set to 300°C or above. When the glass transition temperature is set to 300°C or above, the acid dianhydride or diamine component constituting the polyimide can be appropriately selected.
[0101] As a method for producing a metal-clad laminate having a resin film as an insulating resin layer, for example, there can be cited a method of heat-pressing a metal foil on a resin film directly or via an arbitrary adhesive, or a method of forming a metal layer on a resin film by a method such as metal vapor deposition, etc. Furthermore, a double-sided metal-clad laminate can be obtained, for example, by a method of forming a single-sided metal-clad laminate, and then making polyimide layers face each other and press-bonding them by heat pressing, or a method of press-bonding a metal foil to a polyimide layer of a single-sided metal-clad laminate, etc.
[0102] [Metal layer]
[0103] The material of the metal layer is not particularly limited, and examples thereof include copper, stainless steel, iron, nickel, beryllium, aluminum, zinc, indium, silver, gold, tin, zirconium, tantalum, titanium, lead, magnesium, manganese, and alloys thereof. Among these, copper or copper alloys are particularly preferred. The metal layer may be a metal foil, a film on which metal is evaporated, or a film printed with a paste. In addition, in terms of being able to directly apply the resin composition, a metal foil or a metal plate may be used, preferably a copper foil or a copper plate.
[0104] The thickness of the metal layer is appropriately set according to the purpose of use of the metal-clad laminate, and is therefore not particularly limited. For example, it is preferably in the range of 5 μm to 3 mm, and more preferably in the range of 12 μm to 1 mm. If the thickness of the metal layer is less than 5 μm, there is concern that undesirable conditions such as wrinkles may occur during the transportation of the manufacture of the metal-clad laminate. On the contrary, if the thickness of the metal layer exceeds 3 mm, it will become hard and the processability will deteriorate. Regarding the thickness of the metal layer, generally speaking, a thick metal layer is suitable for applications such as vehicle-mounted circuit substrates, and a thin metal layer is suitable for applications such as LED circuit substrates.
[0105] [Example]
[0106] The following examples are shown to more specifically illustrate the features of the present invention. However, the scope of the present invention is not limited to the examples. Furthermore, in the following examples, unless otherwise specified, various measurements and evaluations are performed as follows.
[0107] [Viscosity measurement]
[0108] The viscosity of the resin solution was measured at 25° C. using an E-type viscometer (Brookfield, trade name: DV-II+Pro). The rotation speed was set so that the torque was 10% to 90%, and the value when the viscosity stabilized was read 1 minute after the start of the measurement.
[0109] [Determination of relative dielectric constant and dielectric loss tangent]
[0110] <Silica particles>
[0111] A vector network analyzer (manufactured by Keysight Technologies, trade name: vector network analyzer E8363C) and a relative dielectric constant measuring device manufactured by Kanto Electronics Application Development Co., Ltd. using a resonant cavity perturbation method were used, set to relative dielectric constant measurement mode: TM020, and the relative dielectric constant (ε1) and dielectric loss tangent (Tanδ1) of the silica particles at a frequency of 10 GHz were measured. The silica particles were in powder form and filled into a sample tube (inner diameter 1.68 mm, outer diameter 2.28 mm, height 8 cm) for measurement.
[0112] <Resin film>
[0113] The relative dielectric constant (ε1) and dielectric loss tangent (Tanδ1) of the resin film at a frequency of 10 GHz were measured using a vector network analyzer (Keysight Technologies, trade name: Vector Network Analyzer E8363C) and an SPDR resonator. The resin film used in the measurement was left for 24 hours at a temperature of 24°C to 26°C and a humidity of 45% to 55%.
[0114] [Determination of coefficient of thermal expansion (CTE)]
[0115] For a resin film of 3 mm × 20 mm size, a thermomechanical analyzer (manufactured by Bruker, trade name: 4000SA) was used to increase the temperature from 30°C to 265°C at a certain heating rate while applying a load of 5.0 g, and then maintained at the temperature for 10 minutes, and then cooled at a rate of 5°C / min to determine the average thermal expansion coefficient (thermal expansion coefficient, CTE) from 200°C to 100°C.
[0116] [Measurement of particle size]
[0117] The particle size of the silica particles was measured by laser diffraction-scattering measurement using a laser diffraction particle size distribution analyzer (Malvern, trade name: Master Sizer 3000) with water as the dispersion medium and a particle refractive index of 1.54.
[0118] [Determination of true specific gravity]
[0119] The true specific gravity of the silica particles was measured by a pycnometer method (liquid phase replacement method) using a continuous automatic powder true density measuring device (manufactured by Seishin Enterprise Co., Ltd., trade name: AUTO TRUE DENSERMAT-7000).
[0120] [Determination of cristobalite crystal phase]
[0121] Using an X-ray diffraction measuring device (manufactured by Bruker, trade name: D2PHASER), the total area of all peaks originating from SiO2 was calculated based on all diffraction patterns (peak position, peak width and peak intensity) originating from SiO2 in the range of diffraction angle (Cu, Kα) 2θ = 10° to 90°. Secondly, the peak position originating from the cristobalite crystal phase was determined, the total area of all peaks of the cristobalite crystal phase was calculated, and the ratio (weight %) to the total area of all peaks originating from SiO2 was obtained. Furthermore, the attribution of each peak was referenced to the database of the International Centre for Diffraction Data (ICDD).
[0122] [Measurement of circularity]
[0123] The average circularity of the silica particles was measured by dynamic flow particle image analysis using a wet flow particle size and shape analyzer (manufactured by Sysmex Corporation, trade name: FPIA-3000).
[0124] [Evaluation of bending properties]
[0125] According to Japanese Industrial Standards (JIS) K5600-5-1, the center of the long side of a 5 cm × 10 cm resin film is evenly bent for 1 to 2 seconds by winding it around a 5 mm φ metal rod. The resin film that does not break or crack even when bent 180° is rated as "good", and the resin film that breaks or cracks is rated as "unacceptable".
[0126] The abbreviations used in Synthesis Examples, Comparative Examples, and Examples represent the following compounds.
[0127] PMDA: Pyromellitic Dianhydride
[0128] BPDA: 3,3',4,4'-biphenyltetracarboxylic dianhydride
[0129] BAPP: 2,2-bis[4-(4-aminophenoxy)phenyl]propane
[0130] m-TB: 2,2'-dimethyl-4,4'-diaminobiphenyl
[0131] DMAc: N,N-dimethylacetamide
[0132] Filler 1: manufactured by Nippon Steel Chemical & Materials Co., Ltd., trade name: CR10-20 (spherical cristobalite silica powder, circularity: 0.98, cristobalite crystal phase: 98 wt%, true specific gravity: 2.33, D 50: 10.8μm, relative dielectric constant at 10GHz: 3.16, dielectric loss tangent at 10GHz: 0.0008)
[0133] Filler 2: manufactured by Nippon Steel Chemicals & Materials Co., Ltd., trade name: SC70-2 (spherical amorphous silica powder, circularity: 0.98, true specific gravity: 2.21, D 50 : 11.7μm, relative dielectric constant at 10GHz: 3.08, dielectric loss tangent at 10GHz: 0.0015)
[0134] Filler 3: manufactured by Nippon Steel Chemical & Materials Co., Ltd., trade name: SP40-10 (spherical amorphous silica powder, spherical shape, true specific gravity: 2.21, D 50 : 2.5μm, relative dielectric constant at 10GHz: 2.78, dielectric loss tangent at 10GHz: 0.0030)
[0135] (Synthesis example 1)
[0136] 24 g of BAPP (60 mmol) and 230 g of DMAc were added to a 300 ml separable flask and stirred at room temperature under nitrogen flow. After complete dissolution, 6.5 g of PMDA (30 mmol) and 8.7 g of BPDA (30 mmol) were added and stirred at room temperature for 18 hours to obtain a polyamic acid solution A. The viscosity of the obtained polyamic acid solution A was 21,074 cps.
[0137] (Synthesis example 2)
[0138] 19 g of m-TB (90 mmol) and 230 g of DMAc were added to a 300 ml separable flask and stirred at room temperature under nitrogen flow. After complete dissolution, 16 g of PMDA (72 mmol) and 5.3 g of BPDA (18 mmol) were added and stirred at room temperature for 18 hours to obtain a polyamic acid solution B. The viscosity of the obtained polyamic acid solution B was 22,400 cps.
[0139] [Example 1]
[0140] 58.7 g of the polyamic acid solution A and 6.1 g of the filler 1 were mixed and stirred until the same solution was visually observed, thereby preparing a polyamic acid composition 1a (viscosity: 23,000 cps).
[0141] The polyamic acid composition 1a was applied to the copper foil 1 (electrolytic copper foil, thickness: 12 μm) and dried at 130°C for 3 minutes. Then, a stepwise heat treatment was performed from 155°C to 360°C and imidization was performed to prepare a metal-clad laminate 1b. The copper foil of the metal-clad laminate 1b was etched away to prepare a resin film 1c. The relative dielectric constant of the resin film 1c (thickness: 51.6 μm) was 3.04, the dielectric loss tangent was 0.0044, and the bendability was "good".
[0142] [Example 2]
[0143] 70.0 g of the polyamic acid solution B and 7.8 g of the filler 1 were mixed and stirred until the same solution was visually observed, thereby preparing a polyamic acid composition 2a (viscosity: 24,800 cps).
[0144] A metal-clad laminate 2b and a resin film 2c were prepared in the same manner as in Example 1. The resin film 2c (thickness: 46.1 μm) had a relative dielectric constant of 2.78, a dielectric loss tangent of 0.0037, a CTE of 34 ppm / K, and a bendability of "good".
[0145] [Example 3]
[0146] 60.0 g of the polyamic acid solution B and 20.0 g of the filler 1 were mixed and stirred until the same solution was visually observed, thereby preparing a polyamic acid composition 3a (viscosity: 28,400 cps).
[0147] A metal-clad laminate 3b and a resin film 3c were prepared in the same manner as in Example 1. The resin film 3c (thickness: 78.1 μm) had a relative dielectric constant of 2.71, a dielectric loss tangent of 0.0028, a CTE of 34 ppm / K, and a bendability of "good".
[0148] [Example 4]
[0149] 55.0 g of the polyamic acid solution B and 36.6 g of the filler 1 were mixed and stirred until the same solution was visually observed, thereby preparing a polyamic acid composition 4a (viscosity: 29,900 cps).
[0150] After the metal-clad laminate 4b was prepared in the same manner as in Example 1, a resin film 4c was prepared. The resin film 4c (thickness: 117.8 μm) had a relative dielectric constant of 2.56, a dielectric loss tangent of 0.0015, a CTE of 31 ppm / K, and a bendability of "not acceptable".
[0151] [Example 5]
[0152] 50.0 g of the polyamic acid solution B, 6.6 g of the filler 1, and 25.3 g of the filler 2 were mixed and stirred until the same solution was visually observed, thereby preparing a polyamic acid composition 5a (viscosity: 31,000 cps).
[0153] After the metal-clad laminate 5b was prepared in the same manner as in Example 1, the resin film 5c was prepared. The relative dielectric constant of the resin film 5c (thickness: 115.5 μm) was 2.71, the dielectric loss tangent was 0.0017, the CTE was 27 ppm / K, and the bendability was "unacceptable".
[0154] (Comparative Example 1)
[0155] The polyamic acid solution A was applied onto the copper foil 1 , dried at 90° C. for 1 minute, and dried at 130° C. for 5 minutes. Thereafter, the solution was heat treated stepwise at 155° C. to 360° C. for imidization, thereby preparing a metal-clad laminate A1 .
[0156] The copper foil of the metal-clad laminate A1 was etched away to prepare a resin film A1 in the same manner as in Example 1. The resin film A1 (thickness: 41.4 μm) had a relative dielectric constant of 3.16, a dielectric loss tangent of 0.0062, a CTE of 51 ppm / K, and a bendability of "good".
[0157] (Comparative Example 2)
[0158] 56.2 g of the polyamic acid solution A and 5.5 g of the filler 2 were mixed and stirred until the same solution was visually observed, thereby preparing a polyamic acid composition A2 (viscosity: 23,600 cps).
[0159] A metal-clad laminate A2 and a resin film A2 were prepared in the same manner as in Example 1. The relative dielectric constant of the resin film A2 (thickness: 50.7 μm) was 3.04, the dielectric loss tangent was 0.0047, and the bendability was "good".
[0160] (Comparative Example 3)
[0161] 56.2 g of the polyamic acid solution A and 5.5 g of the filler 3 were mixed and stirred until the same solution was visually observed, thereby preparing a polyamic acid composition A3 (viscosity: 30,000 cps).
[0162] After preparing the metal-clad laminate A3, the resin film A3 was prepared in the same manner as in Example 1. The relative dielectric constant of the resin film A3 (thickness: 45.6 μm) was 3.25, the dielectric loss tangent was 0.0052, the CTE was 41 ppm / K, and the bendability was "good".
[0163] The above results are summarized and shown in Tables 1 and 2.
[0164] The so-called crystalline phase in Table 1 refers to the ratio of the cristobalite crystalline phase, and the so-called filler ratio refers to the ratio (weight ratio) of the filler to the whole polyamic acid solution (varnish), or the total solid content of the organic compound and the silica particles (wherein the weight of the polyamic acid is converted into the polyimide after imidization and calculated). In addition, the so-called filler content in Table 2 refers to the ratio (weight ratio) of the filler to the resin film.
[0165] [Table 1]
[0166]
[0167] [Table 2]
[0168]
[0169] It was confirmed that the viscosity of the polyamic acid composition 1a of Example 1 was lower than that of the polyamic acid composition A2 and the polyamic acid composition A3 of Comparative Examples 2 and 3, respectively. In addition, the relative dielectric constant and dielectric loss tangent of the resin film 1c of Example 1 were lower than those of the resin films A2 to A3 of Comparative Examples 2 to 3, and the effect of lowering dielectric constant was confirmed as the ratio of the cristobalite crystal phase was higher.
[0170] From the above results, it was confirmed that the resin film of the present embodiment can be suitably used as a material for a flexible printed circuit board that supports high frequencies.
[0171] As mentioned above, although embodiment of this invention was described in detail for the purpose of illustration, this invention is not limited to the said embodiment, Various deformation|transformation is possible.
Claims
1. A resin composition comprising: a solid component of an organic compound including polyamic acid or polyimide, and silica particles, wherein the resin composition is characterized in that: The polyamic acid or polyimide is a polyamic acid or polyimide containing at least one selected from 2,2'-dimethyl-4,4'-diaminobiphenyl and 2,2-bis[4-(4-aminophenoxy)phenyl]propane as a diamine residue, The content of the silica particles is in the range of 10 wt % to 85 wt % relative to the total amount of the solid content and the total amount of the silica particles, wherein the polyamic acid is converted into imidized polyimide, As for the silica particles as a whole, the ratio of the total area of the peaks derived from the cristobalite crystal phase in the range of 2θ=10° to 90° in the X-ray diffraction analysis spectrum using CuKα rays to the total area of the peaks derived from SiO2 is 80% by weight or more, The median particle size D in the frequency distribution curve of the silica particles obtained by volume-based particle size distribution measurement using a laser diffraction scattering method is 50 In the range of 8μm to 15μm, 90% by weight or more of the silica particles have a true specific gravity of 2.3 or more. 2 . The resin composition according to claim 1 , wherein 90% by weight or more of the silica particles having a particle size of 3 μm or more have a circularity of 0.7 or more.
3. A resin film having a single or multiple polyimide layers, wherein: At least one of the polyimide layers is a crystalline silica-containing polyimide layer formed from the resin composition according to claim 1 or 2, and the thickness of the crystalline silica-containing polyimide layer is within a range of 15 μm to 200 μm. 4 . The resin film according to claim 3 , wherein a ratio of a thickness of the polyimide layer containing crystalline silica to a total thickness of the resin film is 50% or more. 5 . The resin film according to claim 3 , wherein the relative dielectric constant at a frequency of 3 GHz to 20 GHz measured using a post-cleavage dielectric resonator is 3.1 or less. 6 . The resin film according to claim 3 , wherein the dielectric loss tangent at a frequency of 3 GHz to 20 GHz when measured using a split dielectric resonator is 0.005 or less. 7 . The resin film according to claim 3 , wherein the thermal expansion coefficient is 50 ppm / K or less.
8. A metal-clad laminate comprising an insulating resin layer and a metal layer laminated on at least one surface of the insulating resin layer, wherein: At least one layer of the insulating resin layer comprises the resin film according to any one of claims 3 to 7 .
Citation Information
Patent Citations
Electrostatic 4-phase electric field rotating device
JP1988087181A
Thermosetting resin composition, interlayer-insulating resin film, composite film, printed wiring board, and production methods thereof
JP2018012747A
Resin composition for semiconductor encapsulation and semiconductor device
JP2019001937A
Polyamic acid film and production of flexible printed circuit board therefrom
JP1994287326A
Powder for spherical silica filler and manufacturing method therefor
JP2019019222A